2022
DOI: 10.25165/j.ijabe.20221505.6425
|View full text |Cite
|
Sign up to set email alerts
|

Droplets deposition and harvest-aid efficacy for UAV application in arid cotton areas in Xinjiang, China

Abstract: With the development of Unmanned Aerial Vehicle (UAV) sprayers, the application of low-volume spraying of harvest-aid and other agrochemicals to cotton using UAVs is becoming a new agronomic trend worldwide. The effect of spray volume and canopy density for UAV spraying is significant but was rarely studied. In this study, five representative spray volumes were explored to examine the effect of spray volume on deposition and harvest-aid efficacy for cotton using a UAV sprayer. To explore the effect of canopy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wang et al [40] designed a PWM variable spraying system for micro-UAVs and used a wind tunnel with controllable multi-wind speed to test the droplet deposition law of variable spraying for a hovering UAV via the phosphor test method. The test results indicated that the wind speed significantly affected droplet deposition.…”
Section: Electrostatic Sprayingmentioning
confidence: 99%
“…Wang et al [40] designed a PWM variable spraying system for micro-UAVs and used a wind tunnel with controllable multi-wind speed to test the droplet deposition law of variable spraying for a hovering UAV via the phosphor test method. The test results indicated that the wind speed significantly affected droplet deposition.…”
Section: Electrostatic Sprayingmentioning
confidence: 99%
“…The application of plant protection UAVs in wheat, 6,24 corn 16 and rice 23 has been progressively developed, and corresponding operating standards have been formulated. However, there have been relatively few studies where researchers have used plant protection UAVs in cotton, 12,25,26 and other economic crops. 27 Cavalaris et al 12 used a plant protection UAV to study the effects of application volume rate and flight height on cotton defoliation rate, boll opening rate and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Spray coverage, droplet density, and pesticide deposition amount are important indicators for evaluating spray deposition performance (Shan et al, 2022). A large number of studies have used artificial collectors such as Mylar and water-sensitive paper (WPS) to visualize spray droplet distribution (Li et al, 2022a;Wang et al, 2022). However, due to the different wettability of natural plant leaves, artificial collectors cannot truly reflect the spray coverage and droplet density on the target leaf surface, which has also confirmed by our previous research (Xiang, 2020;Jiang et al, 2021;Jiang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%